Microplastic accumulation in the gastrointestinal tracts in birds of prey in central Florida, USA. (September 2020) - Carlin, Julia; Craig, Casey; Little, Samantha; Donnelly, Melinda; Fox, David; Zhai, Lei; Walters, Linda
Abstract: A study was conducted to quantify the abundance of plastic pollution in the gastrointestinal tracts in birds of prey. Data was collected from all birds retrieved from the Audubon Center for Birds of Prey in central Florida, USA from January to May 2018. Individuals were either dead prior to reaching the Center or died within 24 h of arrival with no food consumed during captivity. Sixty-three individuals representing eight species were dissected to extract the gastrointestinal (GI) tract from the esophagus to the large intestine. Microplastics were found in the GI tracts in all examined species and in all individual birds. The overall mean number (±S.E.) of microplastics for species of bird of prey in central Florida was 11.9 (±2.8), and the overall mean number of microplastics per gram of GI tract tissue was 0.3 (±0.1). A total of 1197 pieces of plastic were recorded. Microfibers accounted for 86% of total plastics followed by microfragments (13%), macroplastics (0.7%) and microbeads (0.3%). Most fibers were either clear or royal blue in color. Micro-Fourier-transform infrared spectroscopy (μ-FTIR) found that processed cellulose was the most common polymer identified in birds (37%), followed by polyethylene terephthalate (16%) and a polymer blend (4:1) of polyamide-6 and poly(ethylene-co-polypropylene) (11%). Two bird species, Buteo lineatus ( red-shouldered hawk, n = 28) and Pandion haliaetus (osprey, n = 16), were sufficiently abundant to enable statistical analyses. Microplastics were significantly more abundant per gram in the gastrointestinal tract tissue of B. lineatus, that consumes small mammals, snakes, and amphibians, than in fish-feeding P. haliaetus (ANOVA: p = 0.013). If raptors in terrestrial food webs have higher densities of microplastics than aquatic top predators, then it potentially could be due to a combination of direct intake of plastics and indirect consumption via trophic transfer. Graphical abstract: Image 1 Highlights: GI tracts from 9 species of birds of prey were examined for microplastics (n = 63). Microplastics were found in all examined species and in all individual birds. Mean number (±S.E.) of microplastics per bird was 6.22 (±2.46). Rayon was the most abundant polymer found (37%) via FTIR spectroscopy. Abstract : Microplastics were present in all examined birds of prey in central Florida with an overall mean number (±S.E.) of 11.9 (±2.8) per bird. Fish-eating osprey had significantly less plastic in their digestive tracts than terrestrial-foraging red-shouldered hawks.